Evaluación de los animales en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en la parroquia IGNACIO FLORES. - Achig Tarco, Jessica Yolanda (2023)
This research, carried out in Ignacio Flores parish, is focused on the evaluation of cattle characteristics to have better genetics with the same animals in the sector through data collection on each visit to the producers, which allowed to obtain information of production, reproduction, nutrition, management and health of animals, the people of the parish are dedicated in 67% to the raising and care of dairy cattle, the average age of the producers is between 35 and 62 years, who have seen in this a source of income to support their family, most are the elderly people who do not have adequate knowledge about bovine genetic improvement and the benefit that it brings, that is why this project is carried out to help them take better way care and management with a complete record of production and reproduction and thus be able to evaluate characters that are of importance for genetic improvement. Based on the previous information, there are selection criteria that are important for the genetic improvement of the dairy cattle, taking into account each of the variables that are of importance in this sector, such as the nutrition, environment, and characteristics of milk, all these variables are essential for the selection, having good nutrition with balanced and complete food can be improved phenotypically. The predominant race in the sector is the Holstein since it has been shown to have good productive characteristics; the environment is also critical since cattles must adapt to the climate that is varied in seasons; the characterization of milk must be within the parameters because they must be optimal to offer a better quality product and therefore profitability will be better with the proper management of animals, the cost of milk in the sector is 0.42 CTVS., this seeks to have better characteristics, both phenotypic and genotypical, that will give better production and profitability to producers.